1988
DOI: 10.1111/j.1365-2141.1988.tb02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective growth response to IL‐3 of a human leukaemic cell line with megakaryoblastic features

Abstract: A new human leukaemic cell line (M-O7) with the phenotypic characteristics of CFU-mega is described. Its cells are positive for T200 leucocyte common antigen (LCA) and negative with MAbs recognizing T and B cells and mature myelomonocytic antigens. In contrast, they react with MAbs recognizing antigenic determinants common to multi-lineage (CD13, CD33, CD34) and to bipotent erythromegakaryoblastic (CD36, H25) haemopoietic precursors, and with MAbs specific for platelet glycoproteins (CD41w, CD42w). A small pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(116 citation statements)
references
References 32 publications
(9 reference statements)
3
112
1
Order By: Relevance
“…We therefore performed virus-binding assays to investigate the ability of our SCF-eco viruses to bind to the c-kit-expressing cell line, MO7e. 22 As shown in the left panel of Figure 2A, anti-SU monoclonal antibody did not detect binding of normal ecotropic retrovirus to MO7e cells. Using SCF-eco virus, however, we observed a clear shift in fluorescence (Figure 2A right), indicating that the engineered virus was bound to the c-kit ϩ target cells.…”
Section: Redirection Of Retroviral Bindingmentioning
confidence: 80%
See 1 more Smart Citation
“…We therefore performed virus-binding assays to investigate the ability of our SCF-eco viruses to bind to the c-kit-expressing cell line, MO7e. 22 As shown in the left panel of Figure 2A, anti-SU monoclonal antibody did not detect binding of normal ecotropic retrovirus to MO7e cells. Using SCF-eco virus, however, we observed a clear shift in fluorescence (Figure 2A right), indicating that the engineered virus was bound to the c-kit ϩ target cells.…”
Section: Redirection Of Retroviral Bindingmentioning
confidence: 80%
“…TF-1 was supplemented with 1 ng/mL granulocyte-macrophage colonystimulating factor (GM-CSF). The human megakaryoblastic leukemia cell line MO7e 22 was maintained in RPMI supplemented with 20% FCS and 10 ng/mL GM-CSF or shifted into medium without GM-CSF but containing 100 ng/mL SCF for experiments where c-kit expression was down-regulated.…”
Section: Human Cell Linesmentioning
confidence: 99%
“…We studied the properties of our HD-Ad5/35 vectors in Mo7e cells, a growth-factor dependent CD34 + erythroleukemia cell line that is often used as a model for erythroid progenitor cells [27]. Cells were infected with HD-Ad5/35.Tet-1 and HD-Ad5/35.Tet-2 at increasing MOIs, and the percentage of GFP expressing cells as well as mean GFP fluorescence levels were measured 24 hours later in the presence and absence of 100 ng/ml Dox (Fig.3).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that erythroid or megakaryocytic differentiation markers are expressed in UT-7 cells stimulated by Epo (49) or by thrombopoietin (50), respectively. TF-1 and HCD57 cells seem to be strictly committed in the erythroid differentiation pathway, whereas Mo7E cells exhibit megakaryocytic characteristics (38,39,41,51). T3Cl2 cells are Friend virus-transformed cells that correspond to erythroid cells blocked at the colony-forming unit erythroid/proerythroblast stage (52).…”
Section: Discussionmentioning
confidence: 99%
“…Before each experiment, the cells were serum-and growth factor-deprived by incubation overnight in Iscove's modified Dulbecco's medium (Life Technologies, Inc., catalog number 31980-022) containing 0.1% deionized bovine serum albumin. HCD57 cells (38), Mo7E cells (39), and TF-1 cells (40,41) were cultivated in ␣-minimal essential medium containing 5% fetal calf serum and complemented with 2 units/ml Epo (HCD57) or 2.5 ng/ml GM-CSF (Mo7E and TF-1). BaF3 (42) and FDCP-1 (43) cells were cultivated in the same medium complemented with 2.5% WEHI-conditioned medium as a source of IL-3.…”
Section: Methodsmentioning
confidence: 99%